Near Field Communication (NFC) Technology Security Vulnerabilities and Countermeasures - Mahinderjit Singh, Manmeet; Aina Afiqah Ku Adzman, Ku; Hassan, Rohail (International Journal of Engineering and Technology, 2018)
Nowadays; the adoption of Internet of things (IoT) technologies and applications in everyday is rising. IoT technology such as Near Field Communication (NFC) is vastly adopted due to its short range frequencies, making it a good candidate for token based security access control applications such as door systems and attendance systems. However, due to the miniature size of NFC tags; its clear text contents and unprotected communication channel between tag-reader-database; NFC technology is prone to security attacks such as the man in the middle; denial of services (DOS) and etc. These attacks lead to leakage of user critical data which could impact any organization adopting NFC applications and technologies. In this paper; NFC vulnerability, causing both security and privacy attacks studies in depth. By focusing on attacks such as DOS and data corruptions; existing risk assessment models are evaluated using Analytical Hierarchy Process (AHP) approach. Best practice in mitigating these attacks is presented as well. A case study on an existing NFC access control application is then used to demonstrate the effectiveness of best practice solutions proposed.Â Â Â